AGRO-MORPHOLOGICAL CHARACTERIZATION OF MILLET PANICUM SP. GROWN IN NORTHERN CEBU, PHILIPPINES - Borbon, Sharon May S.; Pasajae, Genes M.; Rica, Rachel Luz V. (Journal of Agriculture and Technology Management, 2018)
An agro-morphological study of millet locally known as “kabog” and grown in the Northern part of Cebu was undertaken to characterize, identify and relate to commercially known millets (foxtail, pearl, proso and finger millets). The observations were recorded on the morphol ogical traits (leaf blade and leaf sheath colour, leaf angle pubescence, ligule and auricle colour and structures, node and inter node colour, panicle habit, stamen and stigma colour and amount, shape and colour of grains, lemma and palea pubescence, seed coat colour, type of root system, number) and agronomical traits (number of days of seedling emergence, number of days from emergence to panicle initiation, number of days from first panicle initiation to blooming, number of days from blooming to ripening, number of days from ripening to harvesting, number of leaves produce  from  planting to  panicle initiation, panicle height, plant height,  fresh weight  above - ground biomass, fresh weight panicle, number of grain per panicle, dry weight of above -ground biomass,    dry grain weight per panicle, weight of 1000 dry seeds, fresh root weight, dry root weight, root number per plant and diameter of the biggest root).“Kabog” has more or less similar common morphological and agronomic characteristics with proso millet based on the morphological and agronomic performance of the four (4) common cultivated millet species.